2018
DOI: 10.1002/sd.1745
|View full text |Cite
|
Sign up to set email alerts
|

Aligning South Africa's National Development Plan with the 2030 Agenda's Sustainable Development Goals: Guidelines from the Policy Coherence for Development movement

Abstract: Sustainable development depends on coherence between the development policies of recipients and the providers of development assistance. Yet achieving coherence is difficult. This paper examines the extent to which the Policy Coherence for Development movement offers guidelines for aligning national development priorities with global development priorities. This qualitative paper focuses on alignment between South Africa's National Development and its Medium‐Term Strategic Frameworks and the 2030 Agenda and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 15 publications
(20 reference statements)
1
29
0
6
Order By: Relevance
“…Moreover, the government should support public education and project a more positive image of disability within Ghanaian society. This could form part of localized SDG goals to address a context specific problem (Diaz‐Sarachaga et al, ; Fourie, ). This could be done in partnership with the media to educate and sensitize the population about the capabilities of persons with disabilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the government should support public education and project a more positive image of disability within Ghanaian society. This could form part of localized SDG goals to address a context specific problem (Diaz‐Sarachaga et al, ; Fourie, ). This could be done in partnership with the media to educate and sensitize the population about the capabilities of persons with disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…When implementing Goal 1 of the SDG, it is apparent that countries have a crucial role to play when it comes to developing effective social programs to enhance the lives of the poor (Diaz‐Sarachaga, Jato‐Espino, & Castro‐Fresno, ; Fourie, ). This study found that Ghanaian society still envisions persons with disabilities as dependents.…”
Section: Discussionmentioning
confidence: 99%
“…A few researchers have indicated that the soft measures uphold the principle of common but differentiated responsibilities , allowing countries to chart their own sustainability paths and make adaptations based on their institutional learning (Xue, Weng, & Yu, ) and their interpretations of policy integration (Tosun & Leininger, ). The sustainability path may include political commitments to adapt existing institutions for developing long‐term and transnational priorities (Fourie, ). However, the literature lacks empirical studies on the national implementation of SDGs that go beyond the analysis of public documents; such documents may present questionable data.…”
Section: Introductionmentioning
confidence: 99%
“…A inovação dessa agenda de desenvolvimento está em sua escala, complexidade e pretensão de definir meios de implementação e monitoramento que atentam para as relações entre os objetivos traçados, como aponta a literatura (ALCALDE, 2017;BIERMANN, STEVENS, et al, 2015;FOURIE, 2018). Essa característica implica uma diferença significativa para a adesão dos Estados ao compromisso internacional.…”
Section: Introductionunclassified
“…(ONUBR, 2018, p. 17). Fourie (2018) trabalha diretamente com o dilema de alinhar a agenda nacional de desenvolvimento à nova Agenda de Desenvolvimento Sustentável. Nas palavras do autor:…”
Section: Introductionunclassified